If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4t + 16) = (5t + -21) Reorder the terms: (16 + 4t) = (5t + -21) Remove parenthesis around (16 + 4t) 16 + 4t = (5t + -21) Reorder the terms: 16 + 4t = (-21 + 5t) Remove parenthesis around (-21 + 5t) 16 + 4t = -21 + 5t Solving 16 + 4t = -21 + 5t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-5t' to each side of the equation. 16 + 4t + -5t = -21 + 5t + -5t Combine like terms: 4t + -5t = -1t 16 + -1t = -21 + 5t + -5t Combine like terms: 5t + -5t = 0 16 + -1t = -21 + 0 16 + -1t = -21 Add '-16' to each side of the equation. 16 + -16 + -1t = -21 + -16 Combine like terms: 16 + -16 = 0 0 + -1t = -21 + -16 -1t = -21 + -16 Combine like terms: -21 + -16 = -37 -1t = -37 Divide each side by '-1'. t = 37 Simplifying t = 37
| a-3.5=19.5 | | x=4-2x | | 2a-21.2=a+1.8 | | 9x-8+4x=13x-8 | | 3(2x+5)=2(4x-5)3x | | X(x-15)=35 | | 4n+5(7n-3)=9(n-5) | | (6a-4)=(4a+36) | | 6x=7x-9 | | 4x(x+5)-11=4x^2+17x+1 | | 2.3x+6=-4.3x+9 | | 30(x-5)=30 | | 5w+3w=24 | | 5r^2+12z+4=0 | | 2(3h+11)=6h+4 | | 3(2x+5)=-7(3-2x) | | (3e-32)+(e+16)=180 | | 20y+2(5-15y)=0 | | 18(m+6)=15m-6 | | 10x+12y=166 | | 10x-2(x-3)=8(x+1)+9 | | x^2+20x+64=0 | | 4x-2(-5x-6)=138 | | 10x-12y=166 | | -12-12=x | | 100x^2-9=-5 | | 5y-13-2y+8=0 | | p^2-4=-3 | | 7(3n+8)=12n-7 | | 2(4x+5)=2x-8 | | 6(x+8)=5(x-9)+x | | m^2=25 |